Identification of peptides from edible silkworm pupae (Bombyx mori) protein hydrolysates with antioxidant activity. (May 2022) - Cermeño, Maria; Bascón, Carmen; Amigo-Benavent, Miryam; Felix, Manuel; FitzGerald, Richard J.
Graphical abstract: Highlights: Silkworm protein hydrolysates were generated with a range of proteolytic enzymes. The resulting physicochemical properties of the hydrolysates were enzyme dependent. The hydrolysates demonstrated in vitro and in situ antioxidant activity. In total, 8 peptides were synthetised and examined for cellular antioxidant activity. SWFVTPF and NDVLFF showed the highest antioxidant activity in HepG2 cells. Abstract: Silkworm ( Bombyx mori ) pupae is a by-product from the silk industry which is rich in protein. Hydrolysates from silkworm pupae generated using Alcalase®, Prolyve®, Flavourzyme® and Brewers Clarex® proteolytic preparations were characterised. The antioxidant activity of the hydrolysates was investigated using in vitro antioxidant assays and an in situ assay for reactive oxygen species (ROS) reduction using hepatic HepG2. Overall, Alcalase and Prolyve hydrolysates had highest scavenging activities, however, Flavourzyme and Brewers Clarex hydrolysates had enhanced ferric reducing antioxidant power (FRAP) activity compared to the other samples. Furthermore, the Flavourzyme hydrolysate significantly reduced ROS by 40% compared to untreated control HepG2 cells. Peptides identified by LC-MS/MS were synthetised and then tested for their in vitro and in situ antioxidant activity. Peptides SWFVTPF and NDVLFF showed highest antioxidant activity (ROS reduction, superoxide dismutase (SOD) expression and glutathione (GSH) production activity) in HepG2 cells, and therefore may have potential as natural antioxidants.